Organizational communication perspectives and trends - Papa, Michael J.; Daniels, Tom D.; Spiker, Barry K.; Daniels, Tom D.; Sage eBooks (Los Angeles ; London : SAGE, 2008)
The fifth edition of this introductory organisational communication textbook continues to examine and explore the problems and paradoxes of organisational communication, and the changing features of organisational life that have been revealed through the application of pluralistic perspectives.
Previous ed.: published as Perspectives on organizational communication by Tom D. Daniels. 1997.
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: Communication in organizations; Electronic books